Sistem Pendukung Keputusan Penilaian Karyawan Terbaik Dengan Metode SMART Pada AJB. Bumiputera 1912 wilayah Jambi - Toni, Royles; Roestam , Rusdianto (LPPM Universitas Dinamika Bangsa, 2022)
AJB. Bumiputera 1912 is one of the national companies engaged in insurance. Improving the quality of Human Resources, one of which is through the assessment of the best employees, is a non-negotiable priority if the company wants to get maximum business results and loyal employees. So far, the employee performance appraisal process is based on the assessment of the criteria for the last one year that has been determined based on the decision letter of the board of directors and contained in the Work Assessment Sheet (LPK) and the assessment is limited to the basis for determining periodic salary increases. This results in employees not being motivated to give their best and career stagnation. Based on these conditions, a decision support system for selecting the best employees is needed that can help managers determine the best employees based on existing criteria. So the final result of this research is the design of a decision support system for selecting the best employees with the SMART method which aims to facilitate decision makers in determining the best employees accurately and consistently.